Ultra‐wideband imaging with an improved backward projection algorithm for far‐field applications - Xu, Huaqiang; Fan, Yucheng; Li, Xiaoshuang; Liu, Jianwei; Wang, Yumeng; Yu, Xinchang; Zhao, Yuefeng; Wang, Jingjing (Microwave and optical technology letters, 2024)
Ultra‐wideband (UWB) radar imaging is widely used in penetration detection, target location and detection, and vital monitoring because of its high interference immunity and excellent target recognition with high resolution. In this paper, we report the design of a UWB stepper radar imaging system by using a vector network analyzer and a specially designed novel Vivaldi antenna for far‐field imaging applications. An anti‐attenuation backward projection (AA‐BP) algorithm is proposed to alleviate the attenuation impact of electromagnetic wave propagation. The AA‐BP algorithm and the specially designed Vivaldi antenna are jointly applied in our experiments on multiple targets through wall imaging in both free space and multiple‐path propagation environments. The experimental results show that our reported imaging system achieves desirable performances of far‐field imaging.